2015
DOI: 10.1016/j.pop.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivitis

Abstract: Conjunctivitis is the most common cause of red eye in primary care. The 3 most common types of conjunctivitis are viral, allergic, and bacterial, and they can present in either acute or chronic forms; the age of the patient, time of year and physical examination findings are paramount to distinguish the different types of conjunctivitis. Distinguishing between acute viral and bacterial conjunctivitis remains difficult. Patients with prolonged symptoms, poor response to initial management, or evidence of severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 22 publications
2
44
0
6
Order By: Relevance
“…Our data showed that bacterial infection was the most frequent form of infectious conjunctivitis, consistent with the findings of Alfonso et al (Alfonso et al, 2015). The common isolates in this study, C. macginleyi and coagulase-negative Staphylococcus, differed from those isolated in the United States (H. influenza and Streptococcus pneumonia) (Mah, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that bacterial infection was the most frequent form of infectious conjunctivitis, consistent with the findings of Alfonso et al (Alfonso et al, 2015). The common isolates in this study, C. macginleyi and coagulase-negative Staphylococcus, differed from those isolated in the United States (H. influenza and Streptococcus pneumonia) (Mah, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Mild irritation or foreign body sensation may be present in minor diagnoses (conjunctivitis, episcleritis) 1,2. Early viral keratitis, however, may present with irritation only.…”
Section: Historical Featuresmentioning
confidence: 99%
“…Conjunctivitis is defined as infectious or non-infectious inflammation of the bulbar and palpebral conjunctiva 1. Patients typically have a mild burning sensation, tearing, discharge, and associated viral symptoms.…”
Section: Differential Diagnosis For the Acute Red Eye With Normal Lidsmentioning
confidence: 99%
“…Conjunctivitis is also the most common cause of redness of the eye, as the conjunctival tissue (the thin layer that covers the white of the eye) turns red in response to almost any stimuli [2]. Conjunctivitis accounts for 30% of eye complaints and approximately 15% of people experience some form of this disease in their lifetime [3]. In 78-80% of infectious conjunctivitis cases, infection is initiated by bacteria [4].…”
Section: Introductionmentioning
confidence: 99%